The Flourishing of Female-Student Flood Survivors: An Overview of Women's Positive Growth - Etti Isnaini; Siti Urbayatun (Asian Social Work Journal, 2020)
This study aimed to examine the dynamics and factors that influence flourishing in female flood survivors. flourishing is defined as a condition in which life a person experiences happiness and meaningfulness. The research used a qualitative method by in-depth interviews. The subjects were seven female flood survivors who had moderate to high levels of flourishing. The data were analyzed using the thematic analysis by coding the obtained descriptive data. The credibility of the data was confirmed by a significant other as a reliable source that has a thorough understanding of the subject’s life. The results showed that survivors perceived that they flourished because they had a strong motivation to achieve their desired goals. A positive relationship with friends, family, and lecturers lead survivors to perceive that there are no obstacles to attain their goals. Student survivors also play their role as students, family members, and community members seriously (engagement), due to a sense of responsibility towards their own quality of life and success which they perceive is self-determined. A fighting spirit (motivation), a sense of care or concern, gratitude, and a resilient and robust personality are important factors that influence subjects flourishing.